Analisis Yurisdiksi Kriminal Penanganan Tindak Pidana Siber di Wilayah Hukum Kepolisian Daerah Bali - Saskara, Komang Aldi (Lex Lectio Law Journal, 2024)
This cyber crime is also categorized as a transnational crime, because this crime does not recognize borders (borderless) and the time of the incident because the victim and perpetrator are often in different countries. This research will examine the concept and regulation of state criminal jurisdiction for dealing with cyber crimes and whether the concept for dealing with cyber crimes by the police at the Bali Regional Police is ideal. This research uses a type of empirical legal research using several types of approaches including a statutory approach, a conceptual approach and a legal psychology approach. The data sources used in this research are primary data sources and secondary data. The jurisdictional principles that form the basis for the application of criminal law in Indonesia to cyber crimes include the territorial principle and the protection principle. Meanwhile, the current concept of dealing with cyber crime is seen from the jurisdictional aspect, of course to ensnare the perpetrators takes quite a long time and is considered not ideal. It is hoped that the government will ratify the Budapest Convention on cybercrime so that the results of this ratification will become an instrument for Indonesia to collaborate with other countries in applying extraterritorial jurisdiction. The government provides the public with an understanding of ethics and responsibility in interacting in the cyber world by increasing public literacy awareness regarding cyber security. Apart from that, the police need to establish various forms of sustainable partnerships to support the quality of human resources in the IT sector, in addition to getting educated and trained human resources who can support cyber crime investigations.